Relationship Between SGLT-2i and Ocular Diseases in Patients With Type 2 Diabetes Mellitus: A Meta-Analysis of Randomized Controlled Trials - Zhou, Bin; Shi, Yetan; Fu, Rongrong; Ni, Haixiang; Gu, Lihu; Si, Yuexiu; Zhang, Mengting; Jiang, Ke; Shen, Jingyi; Li, Xiangyuan; Sun, Xing (Frontiers in Endocrinology, 2022)
Background: This meta-analysis was conducted to explore the association between sodium-glucose cotransporter 2 inhibitors (SGLT-2is) and ocular diseases in type 2 diabetes mellitus (T2DM) patients. Methods: PubMed, Cochrane Central Registry of Controlled Trials, Web of Science and Springer were searched for articles on randomized controlled trials (RCTs) involving T2DM patients treated with SGLT-2i versus placebo or other hypoglycemic agents published prior to August 2021. The primary outcome of this meta-analysis was incidence of ocular diseases, which was assessed using risk ratios (RR) and 95% confidence intervals (CI). We reviewed 47 papers and compared the effect of SGLT-2i with the effect of the control groups (placebo and other hypoglycemic drugs) on the incidence of ocular diseases. Results: Compared with controls, overall SGLT-2i use in T2DM patients was not associated with incidences of cataract, glaucoma, retinal disease and vitreous disease. Ertugliflozin (RR=0.47, P=0.01) reduced the risk for retinal disease, while empagliflozin (RR=0.44, P=0.05) reduced the risk for diabetic retinopathy (DR) compared with controls. SGLT-2i (RR=0.50, P=0.02), perhaps empagliflozin (RR=0.47, P=0.06), reduced the risk of retinal disease compared with active hypoglycemic agents. Canagliflozin (RR=4.50, P=0.03) increased the risk for vitreous disease compared with placebo. Conclusions: There was no significant correlation between overall SGLT-2i and ocular diseases (cataract, glaucoma, retinal disease, vitreous disease, corneal disease, conjunctival disease, uveal disease, eye haemorrhage and vision problems) in T2DM patients. Ertugliflozin and empagliflozin may protect against ocular diseases, but canagliflozin may promote ocular diseases.